Implementation Of Individual Counseling Services On Self-Control Of K-Pop Fans Students at MAN Pematangsiantar - Mardhiyyah; Suryani, Ira; Rusman, Abdul Aziz (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to describe the implementation of individual counseling services to self-control of K-Pop fan students at MAN Pematangsiantar. The subjects in this study were three K-Pop fan students, the guidance of teachers and homeroom teachers. This research is a type of descriptive qualitative research. Data was collected through observation, interviews and documentation. The results of the study show that: 1) The implementation of individual counseling services to control K-Pop fan students is carried out like the implementation of individual counseling services in general and there is nothing special. The implementation also consists of three stages, namely the initial stage, the middle stage (work stage) and the final stage (action stage). 2) The level of self-control of students using K-Pop in the aspects of cognitive control and decision control is quite good but for the behavioral aspects of control it is still at a low level because in terms of behavior the controller is an external factor. 3) The obstacles in the implementation of individual counseling services are the absence of special guidance counseling hours, the incompatibility of the ratio of the number of counseling teachers with students and the students themselves who are reluctant to carry out individual counseling services.